2022
DOI: 10.3389/fped.2022.1024699
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum on: Pediatric COVID-19: Report from Indonesian pediatric society data registry

Abstract: In the published article, the text in the first paragraph, Methods section showed an incomplete information on the intention of the original data collection and incomplete information on the information comparing the original data with Ministry of Health (MOH) COVID-19 data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…The study in the United Kingdom reported that only 0.9% of pediatric patients infected with COVID-19 were hospitalized, while there were 2% in China and 1.7% in North America. The death cases in this current study reached 10%, which was lower compared to the national data, and two tertiary referral hospitals in Indonesia also reported 46% and 40% respectively 10,11 .…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The study in the United Kingdom reported that only 0.9% of pediatric patients infected with COVID-19 were hospitalized, while there were 2% in China and 1.7% in North America. The death cases in this current study reached 10%, which was lower compared to the national data, and two tertiary referral hospitals in Indonesia also reported 46% and 40% respectively 10,11 .…”
Section: Discussioncontrasting
confidence: 83%
“…Meanwhile, previous national study data recorded that most cases of child mortality were at the age of 10-18 years, i.e. 42 out of 159 cases (26%), followed by the age of 29 days to 1 year reaching 23% 10 . One hypothesis explains that infants have a higher risk because their immune systems are still underdeveloped and will fully mature in the first 7-8 years of life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation